How Does the Repo Market Behave Under Stress? : Evidence From the COVID-19 Crisis - Huser, Anne-Caroline.; Lepore, Caterina; Veraart, Luitgard (Washington, D.C. : International Monetary Fund, 2021)
We examine how the repo market operates during liquidity stress by applying network analysis to novel transaction-level data of the overnight gilt repo market including the COVID-19 crisis. During this crisis, the repo network becomes more connected, with most institutions relying on existing trade relationships to transact. There are however significant changes in the repo volumes and spreads during the stress relative to normal times. We find a significant increase in volumes traded in the cleared segment of the market. This reflects a preference for dealers and banks to transact in the cleared rather than the bilateral segment. Funding decreases towards non-banks, only increasing for hedge funds. Further, spreads are higher when dealers and banks lend to rather than borrow from non-banks. Our results can inform the policy debate around the behaviour of banks and non-banks in recent liquidity stress and on widening participation in CCPs by nonbanks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Banks; Depository Institutions; Financial Crises; Foreign Exchange; Micro Finance Institutions; Network Formation and Analysis